Top quark pair Production : precision measurements of the top quark pair Production Cross Section in the Single Lepton Channel with the ATLAS Experiment - Henrichs, Anna Christine (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
Before any kind of new physics discovery could be made at the LHC, a precise understanding and measurement of the Standard Model of particle physics' processes was necessary.   The book provides an introduction to top quark production in the context of the Standard Model and presents two such precise measurements of the production of top quark pairs in proton-proton collisions at a center-of-mass energy of 7 TeV that were observed with the ATLAS Experiment at the LHC. The presented measurements focus on events with one charged lepton, missing transverse energy and jets. Using novel and advanced analysis techniques as well as a good understanding of the detector, they constitute the most precise measurements of the quantity at that time.